Row crop fields provide mid‐summer forage for honey bees. Issue 6 (6th June 2022) - Silliman, Mary R.; Schürch, Roger; Malone, Sean; Taylor, Sally V.; Couvillon, Margaret J.
Abstract: Honey bees provide invaluable economic and ecological services while simultaneously facing stressors that may compromise their health. For example, agricultural landscapes, such as a row crop system, are necessary for our food production, but they may cause poor nutrition in bees from a lack of available nectar and pollen. Here, we investigated the foraging dynamics of honey bees in a row crop environment. We decoded, mapped, and analyzed 3459 waggle dances, which communicate the location of where bees collected food, for two full foraging seasons (April–October, 2018–2019). We found that bees recruited nestmates mostly locally (<2 km) throughout the season. The shortest communicated median distances (0.474 and 0.310 km), indicating abundant food availability, occurred in July in both years, which was when our row crops were in full bloom. We determined, by plotting and analyzing the communicated locations, that almost half of the mid‐summer recruitment was to row crops, with 37% (2018) and 50% (2019) of honey bee dances indicating these fields. Peanut was the most attractive in July, followed by corn and cotton but not soybean. Overall, row crop fields are indicated by a surprisingly large proportion of recruitment dances, suggesting that similar agricultural landscapes may also provide mid‐summer foraging opportunities for honey bees. Abstract : We tracked honey bee foraging in a row crop environment using waggle dance decoding, which communicates the location of where a successful forager found food. Honey bees used these wind‐ and self‐pollinated crops for forage, especially during mid‐summer. Peanuts (yellow), corn (orange), and cotton (blue), but not soybeans (green), were attractive in July to honey bees.